Facile Solvent-Free Preparation of Antioxidant Idebenone-Loaded Nanoparticles for Efficient Wound Healing - HeeSeon Yang; Sohyeon Yu; Jisu Kim; KumJu Baek; Young-Ran Lee; Hye Sun Lee; Won Il Choi; Daekyung Sung (MDPI AG, 2022)
The excessive production of reactive oxygen species (ROS) causes harmful effects, including biomolecular damage and inflammation. ROS due to ultraviolet rays, blue light, and fine dust harm the skin, causing urban-related aging. Therefore, a strong antioxidant that relieves oxidative stress in the skin and removes ROS is required. Idebenone (IB) is a powerful antioxidant but is poorly soluble and thus has low solubility in water, resulting in low bioavailability. In this study, IB-loaded nanoparticles (IB@NPs) were synthesized by loading IB without an organic solvent into nanoparticles that can provide high loading efficiency and stability for solubilization. Indeed, the synthesized IB@NPs exhibited long-term stability through dynamic light scattering, methylene blue staining, and redispersion assays, and IB@NPs prepared with a 5 wt% IB loading content were found to be optimal. The antioxidant activity of IB@NPs evaluated using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay was significantly higher than that of unloaded IB. In addition, IB@NPs showed excellent biocompatibility, inhibited oxidative damage to mouse NIH-3T3 fibroblasts, and reduced intracellular ROS generation according to an in vitro DPPH antioxidant assay. Most notably, IB@NPs significantly promoted wound healing in vitro, as demonstrated by scratch assays. Therefore, as carriers with excellent stability, IB@NPs have potential cosmetic and pharmaceutical applications.